Peranan Program Acara Mutiara Islam Cwm Dalam Membumikan Dakwah Islam Di Kota Sorong - Kahar, Dirfan (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
The CWM Islamic Pearl Event Program is a religious program for the Islamic religion. This program contains lectures from religious teachers in the Sorong Raya area and also presents audiences from various taklim assemblies, associations, and harmony in Sorong Raya. Not only presenting audiences from various broadcast programs, this broadcast also collaborated with the Indonesian Da'i Association (IKADI) Sorong city and also collaborated with the Sorong State Islamic College (STAIN) campus with lecturers who became Muballigh so that the lectures given were not only limited to lectures in everyday life, but also presents lectures from an academic perspective. The pearl show program is a weekly program that airs every Thursday at 20.00 Wit and Re-run on Friday at 10.00 Wit. Therefore the researcher is interested in taking the title "The Role of the CWM Islamic Pearl Event Program in Grounding Islamic Da'wah in the City of Sorong." And what is the role of the CWM Islamic Pearls Program in Grounding Islamic Da'wah in the City of Sorong